PENGEMBANGAN BUKU SAKU MATERI PEMANASAN GLOBAL UNTUK SMP - Yuliani, Fahtria; Herlina, Lina (Journal of Biology Education, 2015)
Abstract Availability of various learning materials will increase studentâs knowledge. Reality in field still limited of learning materials is used in learning process. The aim of this research is to determine global warming pocketbookÂ  which is appropriate to be used as learning materials in Junior High School, and to determine the feasibility and the effectiveness global warming pocketbook to be developed. This research design was Research and Development (R & D). The results assessment of media specialist and materials specialist showed that a global warming pocketbook was well worth the feasibility percentage, respectively for 96,4% and 93,3%. The response percentage of students on product trial was >50%. Student classical learning completeness obtained â¥75% (KKM: â¥75). The response percentage of teacher was >50%. Based on the above results, it can be concluded that global warming pocketbook which is appropriate with necessary of students and teacher is full colour and picture, consists of many exercises and information supported materials. A global warming pocketbook to be developed is feasible and effective for use as a learning materials in learning process. Abstrak Ketersediaan bahan ajar yang bervariasi akan meningkatkan pengetahuan yang diperoleh siswa. Kenyataan di lapangan masih terbatasnya bahan ajar yang digunakan dalam proses pembelajaran. Penelitian ini bertujuan untuk mengetahui buku saku materi pemanasan global yang sesuai digunakan sebagai bahan ajar di SMP, serta mengetahui kelayakan dan efektifitas buku saku materi pemanasan global yang dikembangkan. Penelitian ini dilaksanakan dengan rancangan penelitian Research and Development (R&D). Hasil penilaian ahli media dan ahli materi menunjukkan bahwa buku saku materi pemanasan global sangat layak dengan persentase kelayakan berturut-turut sebesar 96,4% dan 93,3%. Persentase tanggapan siswa pada uji coba produk mencapai >50%. Ketuntasan belajar klasikal siswa mencapai â¥75% (KKM: â¥75). Persentase tanggapan guru mencapai >50%. Berdasarkan hasil penelitian dapat disimpulkan bahwa buku saku materi pemanasan global yang sesuai dengan kebutuhan siswa dan guru adalah buku saku yang penuh warna dan gambar, serta berisi banyak latihan soal dan informasi pendukung materi. Buku saku materi pemanasan global yang dikembangkan layak dan efektif digunakan sebagai bahan ajar dalam pembelajaran. Â